2018
DOI: 10.5114/bta.2018.73561
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing sterilization conditions and growth regulator effects on in vitro shoot regeneration through direct organogenesis in Chenopodium quinoa

Abstract: Chenopodium quinoa Willd. is known as a multipurpose crop that could be employed as an alternative on unsuitable lands with limited water resources such as arid and semi-arid regions. However, the biggest problem in cultivating this plant is contamination by viruses that are carried by quinoa seeds and cause diseases. Therefore, in vitro propagation methods could be applied to produce virus-free plants. The capacity of sodium hypochlorite to sterilize seeds and the regeneration potential of cotyledonary node s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 38 publications
1
27
1
Order By: Relevance
“…In another study, Non-dominated Sorting Genetic Algorithm-II (NSGA-II) was employed to optimize different types and concentrations of disinfectants as well as immersion time for maximizing explant viability and minimizing in vitro contamination in chrysanthemum [33]. However, most studies have found the optimized solution by trials and error [23,34,35]. NSGA-II is the search algorithms inspired by natural selection and genetics concepts.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Non-dominated Sorting Genetic Algorithm-II (NSGA-II) was employed to optimize different types and concentrations of disinfectants as well as immersion time for maximizing explant viability and minimizing in vitro contamination in chrysanthemum [33]. However, most studies have found the optimized solution by trials and error [23,34,35]. NSGA-II is the search algorithms inspired by natural selection and genetics concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Contamination in plant tissue cultures can be produced by various micro-arthropods (mites, trips, and their vectors), microorganisms (filamentous fungi, yeasts, bacteria), viruses, and viroids (Altan et al, 2010; Da Silva et al, 2016a; Hesami et al, 2018c). Therefore, sterilization step is of high paramount during establishing and maintaining plants in in vitro cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Sterilization of equipment should not be a serious deal in a modern and well-equipped laboratory due to the frequent use of novel microwave-based autoclaves (Da Silva et al, 2016a). However, serious problems are made during the disinfection of biological material (e.g., initial explant) that need more attention and time (Hesami et al, 2018c). In addition, tissues can be a significant potential of hosting different microorganisms thus adequate and proper sterilization treatments require prior to in vitro culture initiation (Mihaljević et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, novel biotechnological methods can be employed in order to satisfy the demands of consumers [1,3]. Nowadays, in vitro culture methods as biotechnological tools are applied to the rapid multiplication of rare plant genotypes, micropropagation of disease-free plants, production of plantderived metabolites, and gene transformation [1,[3][4][5].…”
mentioning
confidence: 99%